Analysis of the Japanese-to-Malay Translation of Emotion Words in the Novel Colorless Tsukuru Tazaki (Jurnal Bahasa, 2024)
In translation studies, scholars find the cultural aspects of words and phrases to be among the most challenging issues in translation. Despite cultural aspects being the main focus in translation studies, emotion words have never been recognized as part of this area of study. However, studies on emotion words have highlighted how the expression of these words is influenced by the culture of the said language. Therefore, this study was conducted to identify the most significant emotion words, together with their semantic field, followed by an analysis of the translation of said words into the target language. In this study, frequency was calculated by observing the most significant emotion words. The novel 'Colorless Tsukuru Tazaki' by Haruki Murakami was selected because his works tend to focus on abstract human traits, such as feelings and thoughts. The findings of the study showed that basic emotion words have the lowest frequency and are directly translated. The most significant emotion words featured in the novel are 'koudoku' and 'sougai' from the category of complex emotion words. The translation method used for complex emotion words is a strategy that is partial to the target language because such words have no translation equivalents.Keywords: Emotion words, translation, Japanese, Malay, Haruki Murakami, cultural aspectsFull text: PDF